Innate immunity: the first line of defense against SARS-CoV-2 - Diamond, Michael S; Kanneganti, Thirumala-Devi (Nature immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus (SARS-CoV)-2, continues to cause substantial morbidity and mortality. While most infections are mild, some patients experience severe and potentially fatal systemic inflammation, tissue damage, cytokine storm and acute respiratory distress syndrome. The innate immune system acts as the first line of defense, sensing the virus through pattern recognition receptors and activating inflammatory pathways that promote viral clearance. Here, we discuss innate immune processes involved in SARS-CoV-2 recognition and the resultant inflammation. Improved understanding of how the innate immune system detects and responds to SARS-CoV-2 will help identify targeted therapeutic modalities that mitigate severe disease and improve patient outcomes.